ADAPTATION AND VALIDATION OF THE PSYCHOLOGICAL CAPITAL QUESTIONNAIRE (PCQ) IN ARMENIAN LANGUAGE (A PILOT STUDY) - Voskanyan , K. V.; Papoyan, S. A.; Manukyan, M.A.; Hovsepyan , N. S. (Modern Psychology, 2021)
The article represents the main peculiarities of the process of PCQ (Psychological Capital Questionnaire) adaptation. A pilot study is performed to test the reliability and validity of Psychological Capital Questionnaire (PCQ) on the Armenian population. Psychological Capital (PsyCap) is a personal resource, which is linked with positive individual and organizational outcomes (performance, well-being, attitudes, etc). The study tested the validity between PsyCap and other constructs, such as Big Five personality traits, self-regulation (V. Morosanova), success motivation (T. Ehlers) and system of values (Schwartz). The components of PCQ were examined using correlation analysis on a sample Armenian employee. The results show that the Armenian version of the Psychological Capital Questionnaire is a reliable and valid tool and as a practical implication, PCQ is reliable to be used in the Armenian organizational context.
Keywords: psychological capital, adaptation, validation, correlation, Armenian sample.